Bioleaching of Transition Metals From Limonitic Laterite Deposits and Reassessment of the Multiple Roles of Sulfur-Oxidizing Acidophiles in the Process - Johnson, D. Barrie; Smith, Sarah L.; Santos, Ana Laura (Frontiers in Microbiology, 2021)
Using acidophilic bacteria to catalyze the reductive dissolution of oxidized minerals is an innovative process that facilitates the extraction of valuable base metals (principally cobalt and nickel) from limonites, which are otherwise often regarded as waste products of laterite mining. The most appropriate conditions required to optimize reductive mineral dissolution are unresolved, and the current work has reassessed the roles of Acidithiobacillus spp. in this process and identified novel facets. Aerobic bio-oxidation of zero-valent sulfur (ZVS) can generate sufficient acidity to counterbalance that consumed by the dissolution of oxidized iron and manganese minerals but precludes the development of low redox potentials that accelerate the reductive process, and although anaerobic oxidation of sulfur by iron-reducing species can achieve this, less acid is generated. Limited reduction of soluble iron (III) occurs in pure cultures of Acidithiobacillus spp. (At. thiooxidans and At. caldus) that do not grow by iron respiration. This phenomenon (“latent iron reduction”) was observed in aerated cultures and bioreactors and was independent of electron donor used (ZVS or hydrogen). Sufficient ferrous iron was generated in the presence of sterilized hydrophilic sulfur (bio-ZVS) to promote the effective reductive dissolution of Mn (IV) minerals in limonite and the solubilization of cobalt in the absence of viable acidophiles.